Role of Tamsulosin in Female Lower Urinary Tract Symptoms - Dr. Sanjay P. Dhangar; Dr. Amrapali D. Gosavi; Dr. Sushant S. Gite (SP’z Series New Insights on Urology and Urological Research Part II, 2023)
Introduction: Lower urinary tract symptoms (LUTS) are a common health problem among women in the younger as well as older age group. Around 15.5%–53.7% of the women are affected by LUTS. Voiding dysfunction in women is defined by the International Continence Society and International Urogynecological Association as abnormally slow and/or incomplete urination diagnosed based on symptoms and urodynamic studies. But presently there is a lack of standardized diagnostic criteria and clinical guidelines. So, female LUTS is overlooked and underestimated. Moreover, the pathophysiological mechanism of female LUTS is unknown. Methods: This study was a prospective double-blind placebo-controlled study. It was carried out in the Department of Urology at Tambe Hospital, Sangamner, Ahmednagar, Maharashtra, India. A total of 100 patients were enrolled in the study and were randomly allocated to either tamsulosin group or the placebo group in double blind fashion. The study was conducted for six weeks period. The primary outcome was symptomatic and subjective improvement and improvement of IPSS and quality of life score at the end of the study. The secondary outcomes were improvements in the urinary flow rates and changes in the post void residual urine. The mean changes from baseline and at six weeks between the two groups were noted and compared. Following collection of data, it was analysed by computer software Statistical Package for the Social Sciences (SPSS version 19). Results: The baseline characteristics of each patient in both the groups were measured and were comparable regarding the age, weight, duration of symptoms and the IPSS. There was statistically significant difference in the baseline IPSS between the two groups and there was a very weak correlation between baseline IPSS and mean change from baseline in IPSS in both groups. Three patients lost to follow up in the tamsulosin group (6%), one patient due to no improvement in the symptoms and two due to adverse effect of the drug. In the placebo group, two patients (4%) lost to follow up due to no improvement in the symptoms. Significant improvements were noted in the storage and voiding symptoms in the tamsulosin group (p value <0.01) as compared to the placebo group. Conclusion: Alpha blockers are effective in the treatment of LUTS female patients. The effect of alpha blockers on LUTS in females should be assessed and treated according to the underlying cause. Apart from this, the role of alpha blockers in combination therapy with other drugs like antimuscarinics should also be investigated.